Gender-related affecting factors of prediabetes on its 10-year outcome. Issue 1 (10th May 2016) - Song, Xiaomin; Qiu, Miaoyan; Zhang, Xuan'e; Wang, Haiyan; Tong, Wenxin; Ju, Liping; Gu, Lei; Sun, Siming; Zhang, Hongli; Wang, Weiqing; Tian, Jingyan
Abstract : Objective: To investigate the gender-related affecting factors of prediabetes on its 10-year outcome, in a longitudinal study. Methods and results: This longitudinal population-based study was performed in the Ping Liang community, Yangpu district, Shanghai, between November 2002 and October 2014. There were 334 participants with prediabetes enrolled in the final analysis. While a certain proportion of the prediabetic population progress to diabetes, the majority remain at the same level or even revert to normal glucose regulation. No gender difference was observed in the change of glucose regulation. However, results from an adjusted logistic regression analysis in males showed that physical activity was significantly associated with both elevated odds of reverting to normal glucose regulation (active vs inactive, OR 3.00, 95% CI 1.09 to 8.30) and developing diabetes (OR 0.34, 95% CI 0.13 to 0.92). Age, baseline 2 h glucose, triglycerides and smoking status were also risk factors significantly associated with diabetes development; while for females, waist circumference played a key role in the outcome. Every unit elevation of waist circumference was associated with lower odds of reverting to normal glucose regulation (OR, 0.94; 95% CI 0.89 to 0.98) and higher odds of progressing to diabetes (OR, 1.05; 95% CI 1.01 to 1.10). Baseline hypertension and family history of diabetes carried higher risk for developing diabetes as well. Conclusions: Physical activity in males and waist circumference in females are important factors predicting both progression to diabetes and regression to normal glucose regulation, indicating that more exercise for males and lower waist circumference for females are beneficial for prediabetes to achieve reversion.